A linear cavity Brillouin fiber laser with multiple wavelengths output - Shirazi, Mohammadreza Rezazadeh; Shahabuddin, Nurul Shahrizan; Aziz, Siti Narimah; Thambiratnam, K.; Harun, Sulaiman Wadi; Ahmad, Harith (John Wiley & Sons, 2013)
A linear cavity Brillouin fiber laser (BFL) is proposed and demonstrated for multi-wavelength operation. The BFL uses a single mode fiber (SMF) as a non-linear gain medium and an optical circulator to generate a linear cavity resonator, Two couplers are used to inject the Brillouin Pump (BP) and tap the BFL output respectively. The effect of the coupler ratio on the BFL performance is studied by keeping constant the ratio of the first coupler and varying the ratio of the second coupler. 11 simultaneous lines with a line spacing of 0.8 nm are obtained at a BP of 11.7 dBm and a coupler ratio of 95:5. The laser output is stable at room temperature with 5 lines obtained at above - 30 dBm, and has the largest signal to noise ratio observed at the remaining lines. The proposed BFL has the advantage of being able to operate at any wavelength and is only dependent on the available BP wavelength. A graph is presented. Output spectrum of the linear cavity BFL at various C2 coupling ratios.